Population and distribution patterns of juvenile scleractinian corals in Sempu Island Nature Reserve, East Java, Indonesia - ANDIK ISDIANTO; SYAFRIAL YANUAR ISHAQ; ADE YAMINDAGO; FENI IRANAWATI; ADI TIYA YANUAR; LISA NUR HIDAYAH; KRISTINA MARSELA; WIRASTIKA ADHIHAPSARI; TRI DJOKO LELONO; AULIA LANUDIA FATHAH; DINI ATIKAWATI; BERLANIA MAHARDIKA PUTRI; NOVAR KURNIA WARDANA; SUPRIYADI SUPRIYADI; OKTIYAS MUZAKY LUTHFI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Isdianto A, Ishaq SY, Yamindago A, Iranawati F, Yanuar AT, Hidayah LN, Marsela K, Adhihapsari W, Lelono TD, Fathah AL, Atikawati D, Putri BM, Wardana NK, Supriyadi, Luthfi OM. 2024. Population and distribution patterns of juvenile scleractinian corals in Sempu Island Nature Reserve, East Java, Indonesia. Biodiversitas 25: 3480-3490. Coral reefs, which play a vital role in tropical marine ecosystems, are threatened by anthropogenic and natural stressors, despite their important ecological and economic roles. This study examines the resilience of coral ecosystems through the lens of juvenile coral populations at Floating House Beach, which is part of the Sempu Island Nature Reserve, East Java, Indonesia. Using the Underwater Photo Transect (UPT) method along a 100-meter reference line with a 1 × 1-meter transect, our study found that coral cover was severely damaged, with live coral cover of only 18.67% and 17.61% at two observation stations, which was dominated by the life form CM (Coral Massive) at both stations. However, twelve juvenile coral genera were identified that showed potential for natural recovery, namely Acropora, Favia, Favites, Galaxea, Leptoseris, Montipora, Mycedium, Platygyra, Pocillopora, Porites, Stylophora, and Turbinaria. Juvenile coral densities were low, at 0.55 and 0.88 colonies/m², indicating a very low coral recruitment category with Pocillopora being the most common. Spatial distribution, analyzed using the Morisita Index, showed a predominantly clumped arrangement (Ip>0), indicating non-random aggregation of juveniles. The results of this study highlight the significant impact of environmental stressors on juvenile coral communities and underscore the urgent need for targeted conservation efforts to support coral resilience and recovery.